The Effects of Inspiratory Muscle Training in Lung Cancer Patients: A Scoping Review - Yolanda Kadir; Rahmaningsih Mara Sabirin; Ammar Abdurrahman Hasyim; Roihan Mohamad Iqbal; Siswanto Siswanto (Jurnal Respirasi)
Introduction: Lung cancer is the leading cause of cancer worldwide, with a high mortality rate. Chronic dyspnea promotes a pathologic cycle of decreased activity, which has been shown to limit exercise tolerance and deteriorate quality of life (QoL). Inspiratory muscle training (IMT) is a resistance-based exercise regimen that aims to improve the strength and endurance of the inspiratory muscles, thereby reducing respiratory symptoms. This study aimed to comprehensively review the possible beneficial effects of IMT on various aspects of lung cancer patients.